ATRAUMATIC RESTORATIVE TREATMENT (ART): EXPERIENCE REPORT - Flávia Vieira Alves , Ana; Lídia Lima Silva, Anna; Caroline Ribeiro Lacerda, Anne; Vieira de Melo Carlini , Beatriz; Kaylanne simplicio Oliveira, Laylen; Jordania Lino Figueredo, Lívia; Alves Freitas Cruz, Kádja; Robério Gomes Pereira de Souza, Thawan; de Souza Pereira, Malvina (Health and Society, 2025)
Dental caries is a disease with wide prevalence and impact on the oral health of the population, being considered a public health problem and requiring an intervention, which depending on the extent of this lesion, can be treated with a minimally invasive restoration removing only the infected dental tissue. Therefore, Atraumatic Restorative Treatment has been proposed as a viable alternative to meet this need, in addition to the possibility of serving patients in social vulnerability because it has: high cost-benefit, easy technique and does not require electrical energy. Furthermore, this work aims to report an experience lived in the Oral Health II discipline, estimating for the population of the Monsenhor Bernardino School, in the State of Pernambuco, the prevalence of dental caries; highlight the technique and use of Atraumatic Restorative Treatment, as well as its application. Through the implementation of oral hygiene guidance (OHO), supervised tooth brushing, plaque detection (IHO-S) and topical fluoride application (ATF) in classrooms, dental kits were provided to all students. These kits contained toothbrushes, toothpaste and dental floss, as well as some toys and fun activities on oral care.